The influence of NAFLD on the risk of atherosclerosis and cardiovascular diseases - Wójcik-Cichy, Kamila; Koślińska-Berkan, Ewa; Piekarska, Anna (Clinical and Experimental Hepatology, 2018)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in developed countries and is associated with obesity, dyslipidaemia, diabetes, and metabolic syndrome. Atherosclerosis and cardiovascular diseases are also highly prevalent in this group of patients, due to the presence of shared risk factors. The incidences of coronary artery calcification, hypertension, aortic valve sclerosis, diastolic dysfunction, atherosclerotic plaques, and increased carotid intima-media thickness were more common in patients with NAFLD than in those without. The present paper reviews the medical literature concerning the association between NAFLD and cardiovascular events.